2017
DOI: 10.1021/acs.cgd.6b01541
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Lanthanide Metal–Organic Frameworks with Tunable Color and White Light Emission

Abstract: Three isostructural lanthanide metal−organic frameworks (Ln-MOFs, Ln = Eu 3+ , Tb 3+ , Dy 3+ ) containing Pterphenyl-2,2″,4,4″-tetracarboxylate ligand (H 4 L) with red, green, and blue luminescence were solvothermally synthesized. Thus, a series of mixed Ln-MOFs, (Eu x Tb y Dy 1-x-y )(HL)(H 2 O)(DEF) (DEF, N,N-diethylformamide), were designed and obtained, which displayed highly temperature-tuned emission in the visible region, including white light emission. Additionally, tunable luminescence can also be achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 49 publications
1
30
1
Order By: Relevance
“…These differ from prior literature studies 26,45 , since the characteristic emission intensity of Eu 3+ (616 nm) and Tb 3+ (547 nm) ions in bimetallic Eu 0. 47 Tb 0.63 -CTP-COOH highly depends on various guests (metal ions and VOCs).…”
contrasting
confidence: 99%
“…These differ from prior literature studies 26,45 , since the characteristic emission intensity of Eu 3+ (616 nm) and Tb 3+ (547 nm) ions in bimetallic Eu 0. 47 Tb 0.63 -CTP-COOH highly depends on various guests (metal ions and VOCs).…”
contrasting
confidence: 99%
“…[36][37] It has been demonstrated that, because of their similar chemical behaviors, [38][39] it is possible to design series of hetero-lanthanide coordination polymers in which lanthanide ions are randomly distributed over the metallic sites of the crystal structure. [40][41][42][43][44][45][46] Consequently, it is possible to tune the intensity and the color of the emission of these systems (sometimes called "molecular alloys" 47 ) by varying the relative contents of the different lanthanide ions. Indeed, inter-metallic energy transfers efficiency drastically decreases with the inter-metallic distance and it is commonly admitted that they become negligible when lanthanide ions are more than 10 Å far from each other.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Ln-doped materials in phosphors for cathode ray tubes (CRTs), plasma displays, and so-called fluorescent light bulbs certainly comforts this claim. Ln-based luminescent materials are also particularly suited for producing trichromic light emissions (red, green, blue aka RGB systems) by mixing different Ln ions, mostly due to the purity of the Eu(III), Tb(III), and Eu(II) red, green, and blue characteristic emissions [ 7 , 8 , 9 , 10 ]. Most Ln-based phosphors are composed of inorganic materials, but organic complexes or metal–organic frameworks (MOFs) show growing interests for organic light-emitting diodes (OLEDs) due to the larger derivatisation ability and variations of chemical structures [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%